Lung function in healthy South African adult females - Smith, Emilee (Department of Public Health and Family Medicine, 2015)
Background: Accurate and appropriate spirometry reference values allow for early detection of respiratory illness and perform an important role in monitoring lung health. There is, in general, a scarcity of data from Africa, and the Global Lung Initiative (GLI) has published global reference equations but models did not include data from African studies. The aim of this study was to investigate lung function in a group of healthy South African females and the applicability of the GLI reference equations. Methodology: Maternal lung function testing was undertaken at 6 to 10 weeks post-partum as part of a birth cohort study, the Drakenstein Child Health Study. Pre- and post-bronchodilator spirometry was performed according to a standardised protocol and correlated with clinical information. Bronchodilator response was assessed by repeating spirometry 15 minutes after administration of inhaled 400mcg salbutamol. Results: A total of 462 women were included, mean age 17 years (range 18- 42 years). The GLI reference equations fitted the observed lung function results well for the group of mothers who did not self-report smoking or asthma. There were 64 (14%) mothers with an abnormal Forced Expiratory Volume in 1 Second (FEV 1) result, 60 (13%) mothers with an abnormal Forced Vital Capacity (FVC), and 35 (8%) mothers with an abnormal FEV 1 /FVC ratio. There were 22 (5%) mothers who had reversible FEV 1; the rate of undiagnosed reversibility was 4% of the cohort. High body mass index was associated with a higher risk for poor FVC and FEV 1 /FVC lung function, OR 1.40 (CI: 1.01, 1.65) and OR 1.25 (CI 1.10, 1.95) respectively. Mothers with a higher socio-economic status had better FEV 1 with the adjusted SES OR 0.65 (CI 0.36, 1.08). Conclusions: There was a high prevalence of abnormal lung function in this cohort of South African adult females and a number of cases of undiagnosed reversibility. Spirometry testing is important to diagnose lung disease in South African communities. The GLI's reference equations were appropriate and applicable for a cohort of South African adult women.